Impact of the Paleocene-Eocene thermal maximum on the evolution of larger foraminifera : a new look at an old problem - Pujalte, Victoriano; Payros, Aitor; Orue-Etxebarria, Xabier; Tosquella, Josep; Schmitz, Birger; Martínez-Braceras, Naroa (Facies, 2025)
A global larger foraminiferal turnover (LFT), first identified in the Pyrenees in 1960, occurred around the Paleocene-Eocene boundary. It is characterized by the replacement of Paleocene assemblages dominated by Glomalveolina and Lockhartia (west and east Tethys, respectively), with others typified by Eocene Alveolina and Nummulites. Its relationship with the Paleocene-Eocene Thermal Maximum (PETM), a brief interval of global warming, has been debated at length. This study confirms that the LFT was triggered by the PETM. In the Pyrenean Basin the primary driver of the LFT was the influx of over 100 km3 of predominantly fine-grained siliciclastic sediment into the sea during the PETM, which disrupted the previous long-lasting oligotrophic conditions. Unlike other K-strategists, Alveolina and Nummulites adapted to the new ecological conditions, radiating and expanding during the Eocene. Although no comparable siliciclastic influx occurred in the Tethys Ocean, the LFT also coincided with the PETM in Slovenia and Egypt (western Tethys). The link between both events is attributed to adaptations to fluctuating nutrient levels and increased coastal water productivity. In Pakistan and the Himalayas (eastern Tethys), the replacement of Paleocene assemblages appears to have been gradual, leading to the notion that the LFT was not linked with the PETM, but rather resulted from natural evolution. A re-evaluation of the data demonstrates that before the global warming Alveolina and Nummulites were minor components of the assemblages, but that they rapidly evolved and diversified during the relatively short interval of the PETM, a shift also observed in the Pacific Ocean.
Publisher Copyright: © The Author(s) 2025.
Keywords: Larger foraminiferal turnover; PETM; Pyrenean Basin; Tethys Ocean